2019
DOI: 10.21203/rs.2.10769/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of different frequencies of repetitive transcranial magnetic stimulation (rTMS) on intracranial neurotransmitters in patients with swallowing disorders after cerebral infarction

Abstract: Objective To study the improvements and mechanism of repetitive transcranial magnetic stimulation (rTMS) on swallowing disorders after cerebral infarction. Methods A total of 60 patients with swallowing disorders were randomly assigned to receive high/low-frequency rTMS treatment, another 30 patients without rTMS treatment were included in the control group. The Kubota’s water-swallowing test, video fluoroscopic swallowing study (VFSS), and major intracranial neurotransmitters were analyzed before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…4). Clinical studies of rTMS showed dopamine release induced by most high-frequency stimulation rather than low-frequency stimulation 19,[39][40][41] . Elevation of BDNF expression seems to be significant, as it plays an important role in enhancing spatial working memory in the hippocampus through activation of BDNF-mediated NMDA receptors 42 .…”
Section: Discussionmentioning
confidence: 99%
“…4). Clinical studies of rTMS showed dopamine release induced by most high-frequency stimulation rather than low-frequency stimulation 19,[39][40][41] . Elevation of BDNF expression seems to be significant, as it plays an important role in enhancing spatial working memory in the hippocampus through activation of BDNF-mediated NMDA receptors 42 .…”
Section: Discussionmentioning
confidence: 99%